Understanding and responding to the environmental human rights defenders crisis: The case for conservation action. Issue 3 (1st December 2020) - Bille Larsen, Peter; Le Billon, Philippe; Menton, Mary; Aylwin, José; Balsiger, Jörg; Boyd, David; Forst, Michel; Lambrick, Fran; Santos, Claudelice; Storey, Hannah; Wilding, Susan
Abstract: Close to two thousand environmental human rights defenders have been killed in 57 countries since 2002, with about four losing their lives every week in 2019. Many of these defenders represent Indigenous Peoples and local communities protecting ecosystems from large‐scale environmentally destructive projects. As the positive contributions of Indigenous and local communities to biodiversity conservation become better recognized, so should the losses and risks that they face. Despite major efforts at documenting abuses and protecting defenders, many blind spots and gaps remain. Here, we call for the conservation community to put the protection of defenders at the heart of its strategy to slow down and reverse the current onslaught on the environment. The conservation community can respond in a number of ways including reaching out to its constituencies, working together with the human rights community, and mobilizing its networks, field offices, and presence in remote areas to denounce abuses and counter isolation. In doing so the conservation community can advance the collective agenda bringing together conservation and environment‐related human rights through the Post‐2020 Global Biodiversity Framework.